Pengembangan Media Pembelajaran Multimedia Interaktif pada Materi Ekologi dan Keanekaragaman Hayati Indonesia untuk Peserta Didik Kelas VII di SMP Negeri 2 Darma - Yanto, Rudi; Setiawan, Dena Latif (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this research is to develop and determine the feasibility of interactive multimedia content in science class VII of Indonesia's ecology and biodiversity material. This research uses a Research and Development (R&D) method with a development model called ADDIE. This development model has five phases, namely analysis, design, development, implementation, and evaluation. The sample in this study was taken from 1 (one) class at SMP Negeri 2 Darma which amounted to 25 students. The data collection techniques in this study are observation, interviews, and questionnaires. The end result of this research is the development of products in the form of interactive multimedia content. The development of interactive multimedia was tested through a questionnaire for validation by media experts and obtained a feasibility level of 85% which is included in the